Living Quran di Era Digital Analisis Penggunaan Aplikasi Quran dan Doa dalam Ibadah Ramadhan Selama Pandemi - Nikhlah Ziyadaturrohmah; Siti Nur Azizah; Hikmatul Luthfi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The phenomenon of living Qur'an in the digital era, emphasizing the use of Al-Qur'an and prayer applications during the month of Ramadan during the COVID-19 pandemic. The pandemic situation has forced Muslims to switch to digital media as an alternative to carrying out worship due to limited access to physical places of worship. Using a qualitative approach and ethnographic methods, this study explores how digital applications of the Qur'an and prayers become a new medium in realizing Qur'anic values ​​in everyday life, as well as how users interpret the sacred text through digital platforms. The results of the study show that digital applications not only support personal worship practices but also form online communities that strengthen spiritual bonds amid social restrictions. However, digitalization also raises challenges, such as shifts in religious authority, interpretation of texts, and issues of religious ethics. Therefore, this study emphasizes the importance of an interdisciplinary approach to understanding the transformation of religious practices in the digital era, as well as the need for a critical attitude in using technology so that Qur'anic values ​​are maintained and authentic. The COVID-19 outbreak has caused significant changes in various aspects of life, including the way Muslims carry out worship during the month of Ramadan. The implementation of health protocols and social restrictions limit congregational worship activities in mosques, encouraging Muslims to find other ways to maintain their worship routines and spiritual closeness. In this condition, mobile-based Quran and prayer applications are an effective and appropriate solution. These applications provide easy access to digital Qurans, interpretations, translations, readings from famous reciters, daily dhikr, special prayers, and additional features such as prayer reminders and Qibla direction indicators. More than just a means of worship, these applications also function as a medium for religious learning through short lectures, studies, and Islamic articles. However, users need to be aware of interference such as notifications from other applications and dependence on internet connections. It is important to remember that the role of these applications is as a complement, not a substitute for direct interaction with the mushaf or attendance at the assembly of knowledge if conditions permit. If used wisely and consciously, Quran and prayer applications can be a very meaningful spiritual support for Muslims during Ramadan in the midst of a pandemic situation.